The nervous system: Orchestra conductor in cancer, regeneration, inflammation and immunity - Hubert Hondermarck; Pearl S. Huang; John A. Wagner (FASEB BioAdvances, 2021)
Abstract Although the role of nerves in stimulating cellular growth and dissemination has long been described in tissue regeneration studies, until recently a similar trophic role of nerves in disease was not well recognized. However, recent studies in oncology have demonstrated that the growth and dissemination of cancers also requires the infiltration of nerves in the tumor microenvironment. Nerves generate various neurosignaling pathways, which orchestrate cancer initiation, progression, and metastases. Similarly, nerves are increasingly implicated for their regulatory functions in immunity and inflammation. This orchestrator role of nerves in cellular and molecular interactions during regeneration, cancer, immunity, and inflammation offers new possibilities for targeting or enhancing neurosignaling in human health and diseases.